1
$\begingroup$

I have a system where $H(w) = \dfrac{1}{(1-\frac{1}{4}e^{-jw})(1-\frac{1}{3}e^{-jw})}$. I need its inverse discrete Fourier transform.

My thinking is that I could use partial fraction decomposition to break this into two fractions of the form $\dfrac{1}{(1-ae^{-jw})}$ which I can then inverse Fourier transform to get a result of the form $h[n] = a^nu[n]$

To simplify, I let $x = e^{-jw}$

Thus $H(w) = \dfrac{1}{(1-\frac{1}{4}e^{-jw})(1-\frac{1}{3}e^{-jw})}$ becomes $H(w) = \dfrac{1}{(1-\frac{1}{4}x)(1-\frac{1}{3}x)}$

I then proceeded to solve both of these using Wolfram, expecting the answers to be the same:

enter image description here

enter image description here

I can't figure out how to get from one answer to the other thus confirming both are equal. Any suggestions would be appreciated.

$\endgroup$
1
$\begingroup$

Wolfie's answer is $$-\frac{3/4}{1/x-1/4}+\frac{4/3}{1/x-1/3}+1.$$ Now $$-\frac{3/4}{1/x-1/4}=\frac{3}{1-4/x}=\frac{3x}{x-4} =\frac{12}{x-4}+3.$$ Also $$\frac{4/3}{1/x-1/3}=\frac{4}{3/x-1}=-\frac{4x}{x-3} =\frac{-12}{x-3}-4.$$ Now put these together....

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.